The impact of workspace design on employees' productivity: a case study on the Chief Minister Department Sarawak / Muhammad Arif Hamli and Syed Ismail Wan Drahman - Hamli, Muhammad Arif; Wan Drahman, Syed Ismail (2013)
Every organizations have its own style of workspace design depends on the organization which they feel suit them best for their organization value and environment. There are many types of workspace design like Modern, Classic, low budget, high Tech and Green workspace design. The study examines the impact of workspace design on employees’ productivity in Chief Minister Department Sarawak (CMD). And also we want to investigate the elements that mostly affect employees’ productivity. A cluster sampling technique was use where we had chosen 4 different departments in CMD and 200 respondents were given questionnaires to be filled. We also examine the relationship between workspace designs on employees’ productivity. On the employee’s side, we want to analyse the features that they value in the workplace. Other than that, the recommendations for suitable improvement of working environment in CMD were examine. We also want to examine the relationship between workspace designs and departments in CMD and relationship between level of productivity and workspace design of CMD. The staff participations are very satisfying as they are willing to fulfil the questionnaires and provide some recommendations for improvement of workspace in CMD. The study was done in persistence and consistence and we cannot deny all the weaknesses occurred during the research was conducted.